Petrology of volcanic sequence in the Arroyo Ranquil Huao: Meseta de Somún Curá.. extra-andean patagonia - Remesal, M.B. (2002)
In the northern side of the extra andean Patagonia, in portions of Rio Negro and Chubut provinces, extensive basaltic lava flows plateaux type are exposed. On the southern side of the plateaux, in the Ranquil Huau stream valley, close to Telsen locality, a large succesion of volcanic and vocaniclastic rocks is exposed. The basaltic lava flows of Somuncura Formation and the Basalto La Mesada (Quin̄elaf Superunit) and the volcanisclastic deposits of the Sarmiento Group are exposed in the area. The different groups of basalts are identified by petrographyc and geochemical distinctive features. In the upper level of Somún Curá Formation a basic pyroclastic flow is interbedded. The basic rocks exposed in the medium level of the valley have distinctive characteristics and they are named as Basanitas Ranquil Huao. The analized units have geochemical parameters consistent with the evolution of melt showing that were produced by differents degree of partial melting.